Risk and Return Performance of IPOs : An Analysis - Jindal, Mani (Indian Journal of Research in Capital Markets, 2017)
Initial public offering (IPO) refers to the sale of new shares in the primary market for the first time to the general public. This study collected IPOs that are listed on the National Stock Exchange. This study focused on the IPO price performance, whether it was overpriced or underpriced. The IPO price performance was calculated by IPOs’ post listing data. The IPOs recorded positive returns or negative returns during the study period from January 1, 2014 to November 4, 2015. This study evaluated the IPO risks and return performance by using three different measures, that is, Sharpe’s, Treynor’s, and Jensen’s alpha measures. It also tried to keep an eye on the market index performance during the study period. In this study, it was found that the IPOs were underpriced and the three models also showed superior return performance of IPOs than the market index performance. The investors earned profits from their rational IPO investment decisions. Due to the over-performance of IPOs and risk return analysis, it was concluded that the investments in IPOs was less risky than the benchmark index’s performance in the study period.